Tmetopis revisited: redescription, new synonymies, and revised tribal placement (Hemiptera: Heteroptera: Pentatomidae) - Rédei, Dávid (Zootaxa, 2017)
The genus Tmetopis Kiritshenko, 1947 (Hemiptera: Heteroptera: Pentatomidae: Pentatominae) and its type species T. chinensis Kiritshenko, 1947, distributed in central and southern China, are redescribed and illustrated. The genus is recognized as the probable sister group of Prionaca Dallas, 1851. The following new subjective synonymies and new combinations are proposed: Tmetopis chinensis Kiritshenko, 1947 = Prionaca hunanensis Lin & Zhang, 1989, syn. nov. = P. jiangxiensis Lin & Zhang, 1989, syn. nov. = P. hubeiensis Zhang, Lin & Zhao, 1990, syn. nov.; Prionaca sikkimensis (Mathew, 1969), comb. nov. (transferred from Degonetus Distant, 1902). Tmetopis (currently in Halyini) and Prionaca (currently in Pentatomini) are both transferred into the tribe Degonetini; the diagnostic characters and relationships of both genera and of the tribe are discussed.